Al-Ghazali's Knowledge Classification System in Modern Education: An Analysis of Ihyâ Ulûm al-Dîn - Dianita, Galuh Galuh; Basuki, Basuki (Jurnal Penelitian Pendidikan Islam, 2023)
Referring to historical developments, there is a dichotomy between religious knowledge and general science. Meanwhile, textually all knowledge comes from Allah without dichotomy. This research was conducted to analyze the classification of science according to al-Ghazali in the book Ihya Ulumuddin and to find out how relevant it is to modern education. In this research, the method used is library research which utilizes primary sources and secondary data sources. The primary source used is the book Ihya Ulumuddin by Imam al-Ghazali, while the secondary sources are articles related to the classification of science. The technique used to explore data sources is documentation techniques, namely using content analysis. The results of the research can be concluded as follows: 1) Al-Ghazali differentiated the legal classification of seeking knowledge, namely religious knowledge as fardhu 'ain, which includes the science of monotheism, the science of fiqh, the science of tafsir, the science of hadith, and the science of Sufism. Meanwhile, general sciences as fadhu kifayah include medicine, engineering, economics, animal husbandry, agriculture and others. Even though there are classifications of knowledge, in essence all knowledge comes from Allah and must be studied. 2) Spiritual values ​​combined with the integration of religious knowledge and general knowledge, character development, use of active learning methods, multidisciplinary approaches and integration between technology and ethics have important points in developing Islamic education that suits students' needs in the current modern this context.